(untitled) (Research, Society and Development, 2021)
Environmental conflicts have become a global reality, in Brazil specifically in the State of Pará, it was the scene of great saddening stories for seeking the preservation of natural resources, presenting various categories of conflicts, whether due to the large amount of raw materials or the Arco do logging. The mapping of these conflicts is fundamental for the preservation of a healthy quality of life, therefore, this work aims to spatialize areas of environmental confrontations in the State, taking into account the data from the Atlas of Environmental Justice, which counted 24 occurrences for the area of study, added to data provided by IBGE, as well as the use of Excel and ArcGIS data processing software. It is possible to spatialize the cities of Pará with their type of conflict. Therefore, it is possible to affirm the diversity of conflicts faced in the State, reflecting the challenge of dealing and managing situations, hence it is recommended to expand this type of study, focusing on the efficient management of territories.